Psychological Problems of Preparing Teenagers for Family Life During Education - Yorboboyeva Iroda Bakhriddinovna (Genius Journals, 2022)
One of the reasons for the increase in the number of family conflicts in modern society is that these young people's ideas about family life are not sufficiently formed. The article discusses the problem of psychological preparation of young people for family life. The views of oriental scholars and modern approaches to the development of ideas about the family, the sociopsychological problems of the family are considered.
Keywords: family; values; family preparation; society